Exploring how Australian occupational therapists and physiotherapists understand each other's professional values: implications for interprofessional education and practice. Issue 1 (January 2014) - Aguilar, Alejandra; Stupans, Ieva; Scutter, Sheila; King, Sharron
Abstract This article provides insight into the values Australian occupational therapists and physiotherapists consider essential for their practice and the values that they perceive as important for each other. Findings from a study that employed the Delphi technique to identify the values occupational therapists and physiotherapists consider essential for their practice were compared with interview results that provide insight into how these professionals perceive one another's values. The results from this comparison indicate that occupational therapy and physiotherapy participants have limited knowledge of each other's values. This is evidenced by participants only identifying a minority of the values considered essential within the other profession and not identifying many of the values that guide daily practice within the other profession. The results hold implications for interprofessional education and practice, where knowledge of the values of other professions in the team is essential. To enable interprofessional collaboration, professions need to make their values explicit and provide their students, practitioners and educators with opportunities to learn about their own values and the values of other professions.